P-109 Dying trajectories in 21st century – a sociological research programme outline. (1st September 2015) - Weber, T
Abstract : Background: In the context of last decade's push for "activation" in European politics, research foundations support research on ageing that focusses mainly on "successful ageing". It is a concept that idealises healthy, active and mobile elderly helpfully contributing to society after retirement (and neglects the diversity of health, social classes and social skills). Aim: In Europe life expectancies and age at death are increasing and more people die in extreme old age. Longevity comes with a price. In the course of the demographic change people not only live longer, but die longer, partially also due to more easily treated but not curable diseases. At the same time elderly are more often forced to deal with end of life planning. Therefore more research, especially interdisciplinary research on the end of life is vital, because the demographic change does not only demand a renegotiation of ageing as it is happening, but also a renegotiation of dying. Results: The change occurring in dying trajectories generates new knowledge, places and spaces, as well as practises and care. These processes of transformation take place without adequate interdisciplinary research such as sociology but also demography, architecture, law etc. Discussion: The presentation will offer possible sociological questions, methods and material needed to study the diversity of contemporary dying trajectories. Conclusion: As only a few elderly die, where, when and how as they would have wished, the highly emotional public debates about for instance care home scandals demonstrate the urgency of sociological empirical research.